ANALYSIS OF PSYCHOSOCIAL THROUGH THE SOCIAL INJUSTICE IN UNFORTUNATE EVENTS FILM (2004) - Ajeng Tialin Natasya (LITERA KULTURA : Journal of Literary and Cultural Studies, 2021)
Psychosocial is an important study to be understood and studied by everyone to know oneself as the basis for socializing. This study is also very important for people who have experienced social injustice, like the Baudelaire children, Violet, Klaus, and Sunny. Because the study can help the characters to know themselves to live their new life, their personality development is described through several phases called "The Eight Phases of Man" in Erik Erikson's psychosocial theory. The description of each phase, in theory, shows the importance of the process of developing character identity in social life as a fundamental way to build good social relations with many people and social circles. Based on the results of this study shows that of the eight human phases in Erik Erikson's theory, there are six phases that can be used to explain the personality of the characters. Furthermore, the descriptions reveal that there is one character that stands out the most and dominates the other two out of the three analyzed characters.